Calling in today's world : voices from eight faith perspectives - Cahalan, Kathleen A. (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2016)
The concept of "vocation" or "calling" is a distinctively Christian concern, grounded in the long-held belief that we find our meaning, purpose, and fulfillment in God. But what about religions other than Christianity? What does it mean for someone from another faith tradition to understand calling or vocation? In this book contributors with expertise in Catholic and Protestant Christianity, Judaism, Islam, Hinduism, Buddhism, Confucianism and Daoism, and secular humanism explore the idea of calling from these eight faith perspectives. - from back of book.
Hineini (Here I am) : Jewish reflections on calling / Amy Eilberg -- Called to follow : vocation in the Catholic tradition / Kathleen A. Cahalan -- To follow Christ, to live in th world : calling in a Protestant key / Douglas J. Schuurman -- Divine summons, human submission : the idea of calling in Islam / John Kelsay -- Worship, the public good, and self-fulfillment : Hindu perspectives on calling / Anantanand Rambachan -- The calling of no-calling : vocation in Nikaya and Mahayana Buddhism / Mark Unno -- The cultivation, calling, and loss of the self : Confucian and Daoist perspectives on vocation / Mark Berkson -- Vocation without the supernatural : calling in secular traditions / Edward Langerak.
Includes bibliographical references and index.
Print version record.
Added to collection customer.56279.3
Keywords: Vocation; Vocation -- Judaism; Vocation -- Christianity; Vocation -- Islam; Vocation -- Buddhism; Vocation -- Hinduism; Vocation; Niebuhr Center Common Good Collection; BODY, MIND & SPIRIT / Inspiration & Personal Growth; BODY, MIND & SPIRIT / Spirituality / General; RELIGION / Christianity / General; RELIGION / Devotional; RELIGION / Spirituality; Electronic books